2012
DOI: 10.1016/j.matbio.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Perlecan modulates VEGF signaling and is essential for vascularization in endochondral bone formation

Abstract: Perlecan (Hspg2) is a heparan sulfate proteoglycan expressed in basement membranes and cartilage. Perlecan deficiency (Hspg2−/−) in mice and humans causes lethal chondrodysplasia, which indicates that perlecan is essential for cartilage development. However, the function of perlecan in endochondral ossification is not clear. Here, we report the critical role of perlecan in VEGF signaling and angiogenesis in growth plate formation. The Hspg2−/− growth plate was significantly wider but shorter due to severely im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 65 publications
1
74
0
Order By: Relevance
“…proliferating cells; thrombospondin-2 (Tsp2, also known as THBS2), a marker of periosteum and osteoblasts (Tucker, 1993), and perlecan, which is used to identify cartilage (Arikawa-Hirasawa et al, 1999;Costell et al, 1999;Ishijima et al, 2012). We found that the Ki67 staining increased in the proliferative chondrocyte zone, periosteum, bone collar, and trabecular bone of Panx3 −/− growth plates, compared to their WT counterparts (Fig.…”
Section: Proliferation Of Chondrocytes and Osteoblast Progenitors Is mentioning
confidence: 88%
“…proliferating cells; thrombospondin-2 (Tsp2, also known as THBS2), a marker of periosteum and osteoblasts (Tucker, 1993), and perlecan, which is used to identify cartilage (Arikawa-Hirasawa et al, 1999;Costell et al, 1999;Ishijima et al, 2012). We found that the Ki67 staining increased in the proliferative chondrocyte zone, periosteum, bone collar, and trabecular bone of Panx3 −/− growth plates, compared to their WT counterparts (Fig.…”
Section: Proliferation Of Chondrocytes and Osteoblast Progenitors Is mentioning
confidence: 88%
“…Perlecan (Pln) is one of the more abundant heparan sulfate proteoglycans and is found in several tissues including in the endochondral barrier in bones [105]; however, it is primarily localized in vascular basement membranes. It has a major role in regulating the development of blood vessels, the heart, cartilage, and the nervous system.…”
Section: The Basement Membrane Supports Valve Endothelial Cells and Amentioning
confidence: 99%
“…Perlecan’s interaction with growth factors and receptors is crucial in both normal development and in disease progression. Perlecan in cartilage modulates vascular endothelial growth factor receptor-2 activity to allow vascular invasion for endochondral bone formation (Ishijima et al, 2012). Meanwhile, perlecan in synovial fluid positively regulates TGF-β signaling to induce osteophyte formation in mouse osteoarthritis models (Kaneko et al, 2013).…”
Section: Introductionmentioning
confidence: 99%